Bilateral triple renal pelvis: A case report - Pejčić, Tomislav Predrag; Aćimović, Miodrag; Džamić, Zoran; Maksimović, Helena; Marković, Biljana; Hadži-Djokić, Jovan (Vojnosanitetski pregled, 2015)
Introduction. Triple renal pelvis is an extremely rare variation of the renal collecting system. To the authors’ knowledge, bilateral triple renal pelvis has not yet been described in the literature. Case report. A 55-year-old man was hospitalized due to papillary bladder cancer, detected on ultrasonography. As incidental finding, intravenous urography revealed bilateral triple renal pelvis. Six weeks after transurethral resection of the bladder tumor (TURB) the patient was admitted again, for the second TURB. Computed tomography-urography confirmed the presence of bilateral triple renal pelvis. Conclusion. The unique case of bilateral triple renal pelvis was presented as an extremely rare variation of the renal collecting system.
Keywords: urinary tract; congenital abnormalities; diagnosis